Effect of ghee residue substitute of bakery fat on quality characteristics of pearl millet based biscuit - Vinay G M; Singh, Ashish Kumar (Indian Journal of Dairy Science, 2025)
Conventionally bakery products are prepared from wheat and its derivatives. The awareness of allergy and health complexation associated with gluten and refined wheat flour leads to increased consumption of gluten reduced or gluten free products. Pearl millet flour is rich in dietary fiber, protein and minerals. Pearl millet has been used in this investigation to replace refined wheat flour partially. In this study, pearl millet flour and refined wheat flour were taken at a ratio of 1:1. Ghee residue (GR) is a by-product that is nutrient dense and possesses flavouring properties. The underutilised product is a source of fat, protein and phospholipid, and may find application in chocolate, burfi, sweets and bakery products. GR is used as a fat replacer in the preparation of biscuits. Fat substituted with GR at 0, 10, 15, 20 and 25% levels. The effect of fat substitution with GR on proximate physical, textural and sensory properties was studied.  It reveals the colour (L*) and hardness of the biscuit increased with GR substitution whereas the percentage of fat, redness, browning index and some sensorial properties decreased. Descriptive sensory analysis reveals that biscuits are distinguished from coarseness, browning appearance, toasted and sweet flavour.